Identifikasi Karakteristik Sifat Fisik dan Kimia Tanah Pada Kawasan Rencana Pengambangan Daerah Irigasi Rawa Sabuhur: Identification of Physical and Chemical Soil Characteristics in the Sabuhur Swamp Irrigation Area Development Plan - Eddy Nashrullah; Ulfa Fitriati; Novitasari Novitasari; Elma Sofia; Endah Widiastuti (Acta Solum, 2025)
To increase rice production in Tanah Laut Regency, one of the programs implemented by the Tanah Laut Regency Government is the development of swamp irrigation areas in Sabuhur Village. Sabuhur Village has a large swamp area, which has great potential to be developed as agricultural land. However, the success of this development is highly dependent on the suitability of the soil for use as agricultural land. Therefore, testing the physical and chemical characteristics of the soil is a crucial first step to identify the potential and constraints that may occur. The method used is field sampling and laboratory testing. Based on the test results, it can be seen that the characteristics of the physical and chemical properties of the soil at the research location. In terms of soil physical properties at the location, it can be known that soil permeability ranges from 1.86-3.64 cm/h (silty clay), bulk density ranges from 1.01-1.46 g/cm3 (most have exceeded critical values for agriculture), particle density ranges from 1.9-2.86 g/cm3 (mineral soil conditions), porosity ranges from 38.83%-63.31% (silty clay), and aggregate stability ranges from 14%-62.8%. As for the chemical properties of the soil, the total Fe content ranges between 112.19-507.47 ppm, pyrite content between 0.004-0.053% (small pyrite content), CEC ranges between 16.15-30.81 me/100gr (moderate to high soil clay content), and moisture content ranges between 4.88%-29.03. Therefore, the sampling location is not a swamp area because it is mostly mineral soil with a small moisture content. The observation location is a permanently submerged wetland environment.